Organization Commitment of Nurses at Phrachomklao Hospital, Phetchaburi Province: ความผูกพันต่อองค์การของพยาบาลวิชาชีพโรงพยาบาลพระจอมเกล้า จังหวัดเพชรบุรี - ทับมนเทียน พิมพ์ชนก (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
This research aims to study 1) Organization engagement of nurses at Phrachomklao Hospital, Phetchaburi Province. 2) Relationship in operation factors and organization engagement of nurses at Phrachomklao Hospital, Phetchaburi Province. Sample were nurses at Phrachomklao Hospital, Phetchaburi Province for 146 person. Descriptive statistics were percentage, average, standard deviation. Inferential statistics were Chi square and multiple regression. The study were found that 1) Engagement of nurses at Phrachomklao Hospital, Phetchaburi Province were overall at high level. Average respectively were trust, target acceptation and Organization Core Values, next were wish to be the organization membership. At medium level were trust, target acceptation and Organization Core Values. And 2) factors were in causal relation with organization engagement in operation of nurses at Phrachomklao Hospital, Phetchaburi Province all aspects respectively such as authority support, job description, remuneration, people relation, leadership with statistically significant at .001